Elementary scientific english practice. - Thornley, G.C (Longman, 1967)
Hot metal. -- Sir walter releigh. -- Electric wire. -- Light. -- Flying. -- In a balloon. -- The nine planets. -- Eclipses. -- Switches and fuses. -- Magnets. -- Otto von guericke and the vacuum. -- Galileo. -- Pendulums. -- Earthquakes. -- Thamas Alva Edison. -- Some of the gases. -- Some Arab Scientists. -- Drills and derricks. -- Mineral oil. -- The soil. -- Irrigation. -- A ship's propeller. -- Faraday and his generator. -- Voltage and current. -- Sir Robert Watson Watt. -- The use of Radar. -- Malaria. -- The air brake. -- The atlantic cable. -- Gravitation.